2022
DOI: 10.3390/ijms23179521
|View full text |Cite
|
Sign up to set email alerts
|

Advances of Epigenetic Biomarkers and Epigenome Editing for Early Diagnosis in Breast Cancer

Abstract: Epigenetic modifications are known to regulate cell phenotype during cancer progression, including breast cancer. Unlike genetic alterations, changes in the epigenome are reversible, thus potentially reversed by epi-drugs. Breast cancer, the most common cause of cancer death worldwide in women, encompasses multiple histopathological and molecular subtypes. Several lines of evidence demonstrated distortion of the epigenetic landscape in breast cancer. Interestingly, mammary cells isolated from breast cancer pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 337 publications
0
2
0
Order By: Relevance
“…Despite the importance of epigenetic modifications that occur directly on the DNA strand, noncoding RNAs (ncRNAs) represent a wide and well-orchestrated regulatory mechanism of gene expression. Most (98.5%) of the eukaryotic genome is transcribed into ncRNAs, including microRNAs (21-25 nucleotides in length) and long noncoding RNAs (lncRNA, > 200 nucleotides in length, or lacking an open reading frame of >100 amino acids) [64,65]. Although miRNAs are supposed to act mainly in the cytosol by inhibiting translation, recent research has shown their location, activity and relevance in the nucleus of cells as direct regulators of cell phenotype [66][67][68][69].…”
Section: Pollution Impact On Ncrnasmentioning
confidence: 99%
“…Despite the importance of epigenetic modifications that occur directly on the DNA strand, noncoding RNAs (ncRNAs) represent a wide and well-orchestrated regulatory mechanism of gene expression. Most (98.5%) of the eukaryotic genome is transcribed into ncRNAs, including microRNAs (21-25 nucleotides in length) and long noncoding RNAs (lncRNA, > 200 nucleotides in length, or lacking an open reading frame of >100 amino acids) [64,65]. Although miRNAs are supposed to act mainly in the cytosol by inhibiting translation, recent research has shown their location, activity and relevance in the nucleus of cells as direct regulators of cell phenotype [66][67][68][69].…”
Section: Pollution Impact On Ncrnasmentioning
confidence: 99%
“…Nonmutational epigenetic reprogramming mainly includes chromatin remodeling complexes, histone modifications, non-coding RNAs, and other epigenetic mechanisms. The nonmutational epigenetic reprogramming of breast cancer cells is not restricted to breast cancer cells themselves but comprises three important aspects: epigenetic regulation of stromal cell types in the breast cancer cell microenvironment, epigenetic regulation of breast cancer cell heterogeneity, and epigenetic regulation of the breast cancer cell microenvironment [ 107 ].…”
Section: Mechanism Of Action Of Ginsenosides Altering Breast Cancer H...mentioning
confidence: 99%
“…ABSTRACT: KEYWORDS: Breast cancer; Epigenetics; Therapy.1 | INTRODUÇÃOO CM é o tipo de câncer com maior prevalência em mulheres e com alta taxa de incidência e mortalidade(SARVARI et al, 2022). Ao longo dos anos, os índices de incidência e mortalidade de CM são crescentes, tanto em países em desenvolvimento, quanto desenvolvidos(SARVARI et al, 2022; LI et al, 2019).…”
unclassified
“…ABSTRACT: KEYWORDS: Breast cancer; Epigenetics; Therapy.1 | INTRODUÇÃOO CM é o tipo de câncer com maior prevalência em mulheres e com alta taxa de incidência e mortalidade(SARVARI et al, 2022). Ao longo dos anos, os índices de incidência e mortalidade de CM são crescentes, tanto em países em desenvolvimento, quanto desenvolvidos(SARVARI et al, 2022; LI et al, 2019). Segundo o "Global Cancer Statistics 2020: GLOBOCAN", o CM feminino se tornou o câncer mais comumente diagnosticado, (HER2) e o índice de proliferação (KI-67), são incluídos principalmente na distinção entre os subtipos moleculares, sendo seus resultados obtidos a partir do perfil de expressão gênica(SHER et al, 2022).…”
unclassified